A cross-cultural evaluation of the psychometric properties of information seeking anxiety scale in Pakistani environment - Naveed, Muhammad Asif; Ameen, Kanwal (Malaysian Journal of Library and Information Science, 2017)
This study investigated the psychometric properties of Information Seeking Anxiety Scale (ISAS) of postgraduate students in a Pakistani university. A 47-item ISAS was administered to 297 students, selected through stratified convenient sampling procedure, by visiting each department at the university. An eighty-five percent response rate was achieved through usable returned questionnaires. The principal component analysis (PCA) using varimax rotation yielded six-factor solution to the Information Seeking Anxiety Scale (ISAS), namely, (1) Resource Anxiety; (2) ICT Anxiety; (3) Library Anxiety; (4) Search Anxiety; (5) Mechanical Anxiety; and, (6) Thematic Anxiety. This six factors corresponded to those of Erfanmanesh, Abrizah, and Karim (2012) but differed somewhat with regard to the statements loaded on each factor. Moreover, these six-factors combined together accounted for 52.7 percent of the total variance explained. Seven item were dropped as a result of reliability analysis resulting 40-item instrument. Also, the values of Cronbach’s internal reliability coefficient alpha for overall ISAS and its sub-scales were found satisfactory as recommended by Nunnally and Bernstein (1994). These results demonstrated the psychometric soundness and stability of ISAS when tested with Pakistani postgraduate students recruited from a research-intensive university. More psychometric studies are required before drawing any sound conclusions regarding adequacy of ISAS in assessing information seeking anxiety in Pakistani information users.